The loser's curse - Holt, Charles A.; Sherman, Roger (American Economic Review, 1994)
If the value of a commodity is unknown, a prospective buyer must realize that a bid based on an overestimate of its value is likely to be accepted. In this situation, merely finding out that one’s bid is accepted may cause one to reduce the estimate of a commodity’s value, so an auction can bring a feeling of regret. 1 Acceptance of a bid is an informative event, and failure to incorporate this contingent information into the bidding strategy can lead to excessive bids and subsequent losses, a result widely known as the 2 There is considerable anecdotal evidence that bidders for a prize of uncertain value fall prey to the winner’s curse, and persistent overbidding has also been observed in laboratory experiments. 3 There is a second factor that can also induce overbidding: the thrill of winning. This raises the possibility that overbidding is due to a utility of winning instead of being the result of an irrational failure to anticipate the informational content of a bid’s acceptance. One way to distinguish these explanations is to examine a situation in which the winner’s curse effect is neutralized, to see if bids are still too high. In order to neutralize the winner’s curse, we identify an opposing bias: a situation in which a failure to anticipate the informational content of a bid’s acceptance will cause one to bid below the optimal bid, resulting in a Since the loser’s curse produces underbidding, its effect is the opposite of that arising from the winner’s curse.